Experimental study on optimizing cheese drying and ripening process - Giametta, F.; Sorrentino, E.; Lapenna, A.; Fianza, G. La (International Journal of Agricultural and Biological Engineering, 2012)
The system proposed in this paper consists of humidity and temperature control during the food maturation process by using a dehumidifier equipped with a desiccant rotor containing silica gel. In this system the condensation/drainage stage is omitted since the humid room air is directed out of the cold store (process air) and the dried air is introduced via the dehumidifier inside the cold store. It allows separate control of the humidity and temperature inside the cold store. The experimental results are obtained in real conditions; the weight loss of the products was determined and it was, also, proved that dried products such as cheeses treated by this method retain their fresh color, texture and other organoleptic properties to ensure their final quality.